Trend analysis for organic waste generation at the administration cafe of UiTM Tapah campus / Nurul Husna Jamian and Faridah Zulkipli - Jamian, Nurul Husna; Zulkipli, Faridah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Decomposable organic waste is recognized as one of the main components of waste comprising between 42% to 80.2% of its composition. Organic waste is any biodegradable material originating from either plants or animals and the volume generated is expected to increase in the near future. This study examines a better prediction model for determining the trends in organic waste generation at the administration café of the UiTM Campus in Tapah. The data for organic waste generation was collected and recorded daily from two stalls at the café. The collection process was undertaken over five working days (Monday - Friday) from 4th March to 20th April 2019. The Least Square and Simple Moving Average Models were performed in this study. It was found that the Simple Moving Average Model was superior to the Least Square Model as it yielded consistently lower Root Mean Square Error (RMSE), Mean Square Error (MSE) and Mean Absolute Deviation (MAD) values. The Moving Average showed that the upward and downward trends in organic waste over time and the trend cycle were smoother than the original data.